Assessment of Saliva Specimens' Reliability for COVID-19 Surveillance - Pierri, Biancamaria; Tafuro, Maria; Cuomo, Maria Concetta; Concilio, Denise Di; Vassallo, Lucia; Pierri, Andrea; Ferro, Amedeo; Rofrano, Giuseppe; Gallo, Alfonso; Stasio, Antonio Di; Mancusi, Andrea; Galdi, Lydia; et al. (Frontiers in Public Health, 2022)
Aim of the present study is the assessment of saliva as reliable specimen for SARS-CoV-2 detection by real-time RT-PCR, especially in community mass screening programs. The performance analysis considered 1221 total samples (NP swabs and corresponding saliva), tested by means a reference diagnostic real-time RT-PCR assay. Conflicting results were further investigated with a second, more sensitive, reference assay. Analysis of agreement showed a good concordance (95.82%), with k coefficient value of 0.74 (p<0.001); moreover, a follow-up analysis revealed the presence of viral gene targets in saliva samples at the time point the corresponding NP swabs turned negative. Data obtained proves the reliability of this alternative biofluid for SARS-CoV-2 detection in real-time RT-PCR. Considering the role of saliva in COVID-19 transmission and pathogenesis, and the advantages in the use of salivary diagnostics, the present validation support the use of saliva as optimal choice in large-scale population screening and monitoring of SARS-CoV-2 virus.